2020
DOI: 10.1158/0008-5472.can-19-2080
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell–Derived IL1β Promotes Desmoplasia and Immune Suppression in Pancreatic Cancer

Abstract: ◥Pancreatic ductal adenocarcinoma (PDA) is an aggressive malignancy typified by a highly stromal and weakly immunogenic tumor microenvironment that promotes tumor evolution and contributes to therapeutic resistance. Here, we demonstrate that PDA tumor cell-derived proinflammatory cytokine IL1b is essential for the establishment of the protumorigenic PDA microenvironment. Tumor cell-derived IL1b promoted the activation and secretory phenotype of quiescent pancreatic stellate cells and established an immunosuppr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(185 citation statements)
references
References 52 publications
7
178
0
Order By: Relevance
“…In this regard, Kaplanov et al proved that a combined neutralization of IL-1β and PD-1 was responsible for an astonishing abrogation of tumor development in a mammary carcinoma murine model [61]. Similar results were obtained in a model of ductal pancreatic adenocarcinoma, in which IL-1β interception significantly enhances the antitumor activity of PD-1 blockade [62].…”
Section: Il-1 Is Responsible For Immunosuppressionmentioning
confidence: 79%
“…In this regard, Kaplanov et al proved that a combined neutralization of IL-1β and PD-1 was responsible for an astonishing abrogation of tumor development in a mammary carcinoma murine model [61]. Similar results were obtained in a model of ductal pancreatic adenocarcinoma, in which IL-1β interception significantly enhances the antitumor activity of PD-1 blockade [62].…”
Section: Il-1 Is Responsible For Immunosuppressionmentioning
confidence: 79%
“…A recent study demonstrated that the antibody-mediated neutralization of IL-1β significantly enhanced the antitumor activity of an anti-PD-1 antibody, which was accompanied by increased tumor infiltration by CD8 + T cells, indicating that targeting IL-1β has a beneficial effect on PDAC therapy outcomes 59 . We previously reported that IL-1β expression was upregulated by IL-20 in glioblastoma cells and oral cancer cells 30,35 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IL-6 and its downstream effector STAT3 induce the differentiation of myeloid cells into immunosuppressive MDSCs or M2 TAMs. Furthermore, it negatively regulates neutrophils, natural killer cells, effector T cells, and dendritic cells (reviewed in [ 190 ]).…”
Section: Cancer-associated Fibroblasts (Cafs) As Immunological Modmentioning
confidence: 99%